Impact of PV installation to the fault current level at UiTM distribution system / Mohd Idham Ujang - Ujang, Mohd Idham (2013)
The need for new and more rigorous standards for power quality, islanding protection of the gird interconnection and safety operation has increasing the number of Photovoltaic (PV) system that being connected to the utility grid. The objectives of this research are to study impactof PV installation to the fault current level at UniversitiTeknologi MARA (UiTM) distribution system. In order to analyze this problem, UiTM distribution system has been simulated in Power System Computer Aid Design (PSCAD).